Polymorphisms of MRP2 (ABCC2) are associated with susceptibility to nonalcoholic fatty liver disease - Sookoian, Silvia Cristina (2009)
AIMS: We hypothesized that ABCC2 gene variants may contribute to susceptibility to nonalcoholic fatty liver disease (NAFLD). Additionally, we tested the hypothesis of a relation between gene variants and disease severity. PATIENTS AND METHODS: The study involved 167 individuals: 109 consecutively presenting unrelated patients with features of NAFLD and different stages of disease severity, and a group of 58 healthy individuals. Four tag single-nucleotide polymorphisms (SNPs; rs717620 A/G, rs2756105 C/T, rs2002042 C/T and rs3740066 A/G) representing 46 polymorphic sites (r(2)>.8) were genotyped. Furthermore, two additional SNPs (rs17222723 A/T and rs8187710 G/A) were included. RESULTS: On univariate analysis, after multiple comparison correction by permutation tests, there were significant differences observed in the allele frequencies of rs17222723 and rs8187710 between healthy individuals and NAFLD patients (empirical P=.037 and .035, respectively). Allelic odds ratios [95% confidence interval] for rs17222723 and rs8187710 were 2.80 [1.11-7.04] and 2.80 [1.11-7.04], respectively. When we tested the hypothesis of a relation between gene variants and the clinical and histological spectra of NAFLD by multinomial regression analysis, a significant association was observed with the same markers: rs17222723 (P=.0029) and rs8187710 (P=.015). CONCLUSIONS: Our study suggests a potential role of ABCC2 in susceptibility to NAFLD and disease severity.